Endocrine Responses to Physical Training and Tribulus Terrestris Supplememtation in Middle-Age Men - Chycki, Jakub; Czuba, Miłosz; Gołaś, Artur; Maszczyk, Adam; Michalczyk, Małgorzata; Roczniok, Robert; Wilk, Michał; Zając, Adam (Central European Journal of Sport Sciences and Medicine, 2016)
The aim of this study was to evaluate the effects of steroidal saponin supplementation on blood concentration of T, GH and IGF-1. The research involved 14 men between the age of 45 and 60 years. The duration of the experiment was 12 weeks. There were two series of laboratory tests. Independent tests were conducted at the beginning and after 12 weeks of the intervention. A two-way repeated measures ANOVA revealed a statistically significant effect of the intervention on the following variables: T-Ch (η2 = 0.542), HDL-Ch (η2 = 0.522), LDL-Ch (η2 = 0.587), T (η2 = 0.603), IGF-1 (η2 = 0.512) and GH (η2 = 0.621). Thus, FFM significantly increased while TBF and BM decreased in comparison to pre-intervention levels. The analyzed results indicate that treatment or supplementation of individual hormone deficiencies can be a successful form of counteracting the aging process. Nevertheless, the effects of TT supplementation on the concentration of T as well as GH and IGF-1, requires further studies, especially in middle-aged and older subjects, along with different exercise programs. The analyzed results indicate that treatment or supplementation of individual hormone deficiencies can be a major form of counteracting the aging process.